Beyond Spectacle : Eliza Haywood's Female Spectators. - Merritt, Juliette (University of Toronto Press, 2004)
Beyond Spectacle will cement Haywood's deservedly prominent place in the canon of eighteenth-century fiction and position her as a writer whose work speaks not only to female agency, but to eighteenth-century writers, gender relations, and power politics as well.